2017
DOI: 10.1016/j.ejca.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The utility of anti-Müllerian hormone in the diagnosis and prediction of loss of ovarian function following chemotherapy for early breast cancer

Abstract: AimChemotherapy results in permanent loss of ovarian function in some premenopausal women. Accurate identification in women with hormone-sensitive early breast cancer (eBC) would allow optimisation of subsequent endocrine treatment. We sought to assess whether analysis of anti-Müllerian hormone (AMH) using a sensitive automated assay could identify women who would not regain ovarian function after chemotherapy.MethodsData from women in the Ovarian Protection Trial in Premenopausal Breast Cancer Patients (OPTIO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 34 publications
4
48
1
2
Order By: Relevance
“…AMH is undetectable and shows no recovery in women receiving high-risk treatment: women and children treated with alkylating agents in high doses showed only little recovery of AMH [ 9 , 16 ]. Age has an important impact, with younger women have a higher pretreatment AMH, and a lower risk of undetectable AMH at the end of treatment chemotherapy (65% in women treated for breast cancer aged over 40; 16% in women aged ≤40 years) [ 22 ▪▪ ]. Younger age and higher pretreatment AMH brings a lower risk of chemotherapy-related amenorrhoea [ 17 , 19 , 22 ▪▪ , 23 ] and higher chance of return of menstruation [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…AMH is undetectable and shows no recovery in women receiving high-risk treatment: women and children treated with alkylating agents in high doses showed only little recovery of AMH [ 9 , 16 ]. Age has an important impact, with younger women have a higher pretreatment AMH, and a lower risk of undetectable AMH at the end of treatment chemotherapy (65% in women treated for breast cancer aged over 40; 16% in women aged ≤40 years) [ 22 ▪▪ ]. Younger age and higher pretreatment AMH brings a lower risk of chemotherapy-related amenorrhoea [ 17 , 19 , 22 ▪▪ , 23 ] and higher chance of return of menstruation [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Chai et al ., levels of AMH measured at 2 years after diagnosis had a sensitivity of 96% in predicting menstruation for the subsequent 3 years ( 31 ). In another study by Anderson et al , a sensitivity of 84% was reported for AMH level at the end of chemotherapy to predict premature ovarian insufficiency at 2 years ( 32 ). However, only a few studies have measured ovarian function at 5 years after diagnosis ( 33 ); most studies have less than 2 years of follow-up ( 15 , 18 , 34 , 35 , 36 ), but ovarian function can be recovered 3 years after treatment ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses in women with breast cancer have shown that receiving treatment at a young age and high concentrations of antimüllerian hormone before treatment are predictive of recovery of ovarian function after chemotherapy, albeit with variable relative contributions. 5 , 9 , 14 , 15 Women with breast cancer are generally older (approximate mean age 40 years 5 , 9 , 14 , 15 ) than those with Hodgkin's lymphoma and treatment involves more gonadotoxic alkylating agent-based regimens, resulting in a high probability of premature loss of ovarian function, particularly in women older than 40 years. These differences emphasise the need for defined populations and treatment regimens to analyse the toxic effects of chemotherapeutic regimens on the ovaries and, particularly, recovery.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 , 7 , 8 In the past 5 years, refinements in assay methods have improved their sensitivity, and thus their ability to detect low circulating concentrations of antimüllerian hormone in women after chemotherapy, which were previously undetectable. 13 , 14 How the pretreatment ovarian reserve and the patient's age influence recovery of ovarian function after chemotherapy is unclear, with most data derived from women who have been treated for breast cancer. 5 , 9 , 15 , 16 In this study, we aimed to determine the effect of response-adapted chemotherapy regimens on ovarian function in adult women with Hodgkin's lymphoma, since they are both a younger population and often treated with less gonadotoxic drugs than women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%